Innovative utilization of cell membrane‐coated nanoparticles in precision cancer therapy - Yiling He; Shuquan Zhang; Yaoguang She; Zhaoshan Liu; Yalan Zhu; Qinzhen Cheng; Xiaoyuan Ji (Exploration)
Abstract Cell membrane‐coated nanoparticles (CMNPs) have recently emerged as a promising platform for cancer therapy. By encapsulating therapeutic agents within a cell membrane‐derived coating, these nanoparticles combine the advantages of synthetic nanoparticles and natural cell membranes. This review provides a comprehensive overview of the recent advancements in utilizing CMNPs as effective drug delivery vehicles for cancer therapy. The synthesis and fabrication methods of CMNPs are comprehensively discussed. Various techniques, such as extrusion, sonication, and self‐assembly, are employed to coat synthetic nanoparticles with cell membranes derived from different cell types. The cell membrane coating enables biocompatibility, reducing the risk of an immune response and enhancing the stability of the nanoparticles in the bloodstream. Moreover, functionalization strategies for CMNPs, primarily chemical modification, genetic engineering, and external stimuli, are highlighted. The presence of specific cell surface markers on the coated membrane allows targeted drug delivery to cancer cells and maximizes therapeutic efficacy. Preclinical studies utilizing CMNPs for cancer therapy demonstrated the successful delivery of various therapeutic agents, such as chemotherapeutic drugs, nucleic acids, and immunotherapeutic agents, using CMNPs. Furthermore, the article explores the future directions and challenges of this technology while offering insights into its clinical potential.